CURRENT STATE OF RESOURCE POTENTIAL AND TERRITORIAL INFRASTRUCTURE OF SOUTH ASIAN COUNTRIES - ZHURBA, IGOR; TRIGUBA, TARAS (Herald of Khmelnytskyi National University. Economic sciences, 2021)
International tourism has become an important component of both the world and national economies of many countries. Revenues from tourism are an important source of foreign exchange earnings, and they also expand the balance of payments and GDP. The tourism and hospitality industry creates thousands of new jobs every year, improving the overall standard of living. No less important is the contribution of tourism to the social life of the population. Travel fosters tolerance and respect in people. Tourism is also a step towards expanding one's worldview, because traveling not only restores strength but also increases one's worldview, accumulates experience and new knowledge. Today the development of international outbound tourism is becoming especially important. The COVI-19 pandemic has changed the way we travel. Tourist destinations to which Ukrainian tourists are accustomed cannot accept the number of tourists they usually received. Therefore, the issue of finding and developing new areas of international outbound tourism is becoming important. The current state of resource potential and territorial infrastructure of South Asia in the example of Sri Lanka. The article analyzes the natural resource potential, substantiates the peculiarities of the development of tourist infrastructure of the Democratic Republic of Sri Lanka. The authors use specific examples to substantiate that the tourist and recreational potential of the country is extremely powerful and diverse. The article analyzes and proves that a large number of attractions, rich history, extremely diverse and powerful natural resource potential in particular, well-developed tourist infrastructure make this country attractive to tourists. Thus, the article proves that according to the results of the study it is necessary to saturate the species structure of tours to Sri Lanka, which are offered on the Ukrainian market.
Keywords: natural resource potential; tourist and recreational resources; diving and surfing tourism; national parks; historical and cultural; event; pilgrimage and medical tourism; tourist infrastructure